1986
DOI: 10.1002/hep.1840060428
|View full text |Cite
|
Sign up to set email alerts
|

Subcapsular hepatic necrosis in orthotopic liver allografts

Abstract: Five cases of subcapsular liver necrosis were found in a series of 55 hepatic orthotopic allografts examined at hepatectomy or autopsy during a 3-yr period at Children's Hospital of Pittsburgh. There was a pronounced rise in liver enzymes in the first few days in all of the cases after transplantation followed by a decrease in values in four of the cases over the next few days. All were characterized by an irregular subcapsular band of necrotic tissue involving both lobes, to a variable degree, but most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…12 Moreover, the high incidence of necrotic foci in the subcapsular region, revealed in this study, is most likely derived from the hypoperfusion. 13 The analysis that uses a laser-doppler flowmeter showed a 20% to 50% decrease in the intrahepatic blood flow, which lasted several hours preceding the hepatic necrosis. Histological analysis showed that the sinusoidal lumen was occluded by agglutinated erythrocytes and by aggregated platelets and leukocytes and was also considerably expanded.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, the high incidence of necrotic foci in the subcapsular region, revealed in this study, is most likely derived from the hypoperfusion. 13 The analysis that uses a laser-doppler flowmeter showed a 20% to 50% decrease in the intrahepatic blood flow, which lasted several hours preceding the hepatic necrosis. Histological analysis showed that the sinusoidal lumen was occluded by agglutinated erythrocytes and by aggregated platelets and leukocytes and was also considerably expanded.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple, small, peripheral subcapsular infarcts may be identified by frozen section in otherwise healthy grafts even prior to implantation. Russo and Yunis [7] described liver transplant infarction in pathological examination of grafts in five children; there was a question of injury during the procurement or implantation of each of these grafts. In addition, slow flow, particularly in the perioperative period, may predispose to necrosis in the peripheral or subcapsular regions of the transplant.…”
Section: Discussionmentioning
confidence: 98%
“…The CTHN / group had a statistical association with periportal collar, however the clinical significance is unclear, because periportal collar is a nonspecific CT finding. If periportal collar is indeed related to lymphatic obstruction, interruption of normal lymphatic drainage might be expected with mechanical distortion of the hepatic arteries, due to resection of restraining ligaments of the liver; this mechanism has been implicated as a cause of focal hepatic necrosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…It can result in fulminant liver failure or ascites. 15.5d ) This is a pattern of hepatic infarction that has been noted in pediatric allografts, the exact etiology of which is not clear (Russo and Yunis 1986 ). (Fig.…”
Section: Portal Vein Thrombosismentioning
confidence: 95%